The Pennsylvania Railroad : the long decline, 1933-1968 - Churella, Albert J., 1964- (Bloomington, Indiana : Indiana University Press, 2024)
"The final volume of Albert Churella's monumental history of the Pennsylvania Railroad, this book begins with the height of the era of steam locomotives and follows the railroad through the turn of the century until its ultimate collapse and demise in 1968"--
"The final volume of Albert J. Churella's landmark series, The Pennsylvania Railroad, concludes the story of the iconic transportation company, covering its long decline from the 1930s to its merger with the New York Central Railroad in 1968.Despite some parallels with World War I, the experience of World War II had a substantially different impact on the Pennsylvania Railroad. The introduction of new technologies, personnel, and commuter routes had significant effects on this giant of American transportation. The recession of 1958 sparked a period of decline from which it and many other railroads struggled to fully recover.The Pennsylvania Railroad: The Long Decline, 1933-1968 provides an unparalleled look at the final years of this legendary company, which in its prime was the largest corporation in the world, with a budget second only to that of the US federal government"--
Steam -- Wired -- Adversaries -- Power -- Renewal -- Decline -- Commutation -- Merger.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Pennsylvania Railroad -- History; Railroads -- Pennsylvania -- History; TRANSPORTATION / Railroads / History; TRAVEL / Food, Lodging & Transportation / Rail Travel; Electronic books; Electronic books